Effect of Impacts on Human Head - Svoboda, Martin; Soukup, Josef; Jelen, Karel; Kubový, Petr (Manufacturing Technology Journal, 2015)
The article deals with experimental measurements of force effects that direct blow develops taekwondo sportsman. Power effects are captured using a high speed camera. Experimental measurements have confirmed the results of many scientific papers that deal with the measurement of the force effects of combat sports athletes, etc. There are described some methods that are used in medicine and biomechanics to view internal organs or injury detection.
Keywords: biomechanics; impact; deformation; measurement; human head